Os saberes docentes para a prática pedagógica de alunos com necessidades educativas especiais na escola regular - Silva, Adarita Souza da (2014)
This research discusses that teaching knowledge which teachers mobilize in the pedagogical practice of students with special educational needs- NEE in regular schools from public schools in the city of Feira de Santana-BA. To achieve the proposed objective we chose a qualitative approach, by providing the enlarge of the discussion about the natural environment of research and enrichment of the description of the data. To this end, a theoretical framework was built, supported by studies by Tardif (2002), Pimenta (2005), Freire (2004), Shulman (2005) and Barth (1993) which underlie the idea that teachers are knowledge developed during the training process and incorporates historical, social, cultural aspects that qualify and re-signify the teaching required teachers to work with such knowledge. Teachers who work with students with special educational needs attribute to knowledge an important element in the construction of pedagogical practice and performance with the included. In this context, therefore, the study of teaching practice for students with NEE lies trampled in reflection about their own teaching educational action (SCHON in NOVOA 1995), as well as subsidies on the concepts of habitus and campus in Bourdieu (1998) . The present study allowed also to know the context in which the research took place, the actions of the subjects inserted and the research space. From the results achieved, we realize that although education policy point advances in the conceptions directed inclusion for students with NEE there are still many conflicts teachers face in concreting ideas of education of these subjects. The subjects also, in his speeches, staked limitations in training to work with students with NEE and had knowledge that comprise pedagogical practice in order to nurture the learning of these students. This knowledge run of varied hues and contexts in order to establish consistency between the know-how and the know-to be-pedagogic in an attempt to develop the intellectual skills of students with NEE towards the improvement of skills, attitudes and knowledge.